Ancient Family Names in the Onymic System of the Slavonic and Baltic Languages - Gurskaja, Julia (Respectus Philologicus, 2012)
This article considers the problem of the formation of ancient family names in the modern Belarus area, which are investigated in their areal, topological and comparative historical aspects. In the article, the time of the appearance of ancient family names in the territory of Belarus, their semantics and structure are analysed, and their connection to the toponyms of the investigated region is revealed. The organized corpus of family names is characterized by the following features: 1) early inclusion in written monuments; 2) the presence of the appropriate family names in other Indo-European languages; 3) lexemes as a part of family names may be interpreted on the basis of their Indo-European roots; 4) diversity of the family name; 5) the presence in the composition of a family name of components correlated with another onym group: toponyms, ethnonyms or hydronyms. The majority of ancient family names in the Belarus territory were formed during the time of the Grand Duchy of Lithuania. The formation of the knightly clans dates from the end of the 14th and the beginning of the 15th centuries and is connected with the state activities of the Great Lithuanian Prince Vitovt. Among the family names of that time, those formed on the basis of ancient complex Indo-European names can be singled out. These family names correspond to family names in the Lithuanian language. A majority of these names have Slavonic formants. Ancient family names going back to the binomial anthroponyms are not distributed evenly throughout the modern Belarus area. One can mark out two territories of high productivity: 1) the Baltic–Slavonic frontier, and 2) the central part of Belarus. As one moves further away from the Baltic–Slavonic frontier, the investigated units change their structure and undergo adaptations. Individual family names still preserve ancient forms with the connecting vowel [i] -i-: Жыг-i-монт, Радз-i-вiл, Эйс-ы-монт, etc. A considerable number of ancient family names made their marks in the conceptual picture of the world of the Belarusian people. These units have brought the modern Belarus area into the broader European context and contributed to the preservation of historical and cultural memory.